Enhancing urban agriculture networks: A clustering and multicriteria decision-making approach to sustainability indicators and governance - Jiangwei Kong; Mengxi Gao; Hind Alofaysan; Dilafruz Fayziyeva; Zhi Liu (Ecological Indicators)
Patterns of environmental, social, and economic sustainability interact across several aspects of an urban area. Accelerated population increase necessitates improved resource management techniques that address the equilibrium of supply and demand in the food, energy, and water sectors while also considering social and economic development. Advancing sustainable development objectives necessitates governing frameworks and operations within and within the food, energy, and water sectors, particularly in light of polycentric urban expansion. This research highlights food security via an urban agricultural network in the larger Miami metropolitan region, which includes Palm Beach, Broward, and Miami-Dade counties. Utilizing the current governance framework, we measured various sustainability indices for clustering analysis to aggregate urban agricultural sites (UASs) and to ascertain the prioritization of clusters based on their vulnerability or risk level as indicated by their priority index in multicriteria decision-making. Eight clusters were chosen for the display of UASs rated using multicriteria decision-making, focusing on scenarios prioritized for governance in light of climate change, social fairness, and economic development consequences. The significance of governance structure in promoting incentive programs to improve the sustainability performance of UASs within an urban food–energy–water nexus was emphasized.